2020
DOI: 10.1093/mnras/staa3618
|View full text |Cite
|
Sign up to set email alerts
|

The impact of merging on the origin of kinematically misaligned and counter-rotating galaxies in MaNGA

Abstract: Galaxy mergers and interactions are expected to play a significant role leading to offsets between gas and stellar motions in galaxies. Herein we crossmatch galaxies in MaNGA MPL-8 with the Dark Energy Spectroscopic Instrument (DESI) Legacy Surveys and identify 311 merging galaxies that have reliable measurements of the ΔPA, the difference between the stellar and gas kinematic position angles to investigate the impacts of merging on gas-stellar rotation misalignments. We find that the merging fractions of misa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…Our blueberry galaxy has disturbed kinematics, showing a misalignment of ∼ 30 o between the stellar and gaseous kinematic major axes. In general, such kinematic misalignment in galaxies indicates signs of galaxy interaction and merger or external gas accretion (Jaiswal & Omar 2013;van de Voort et al 2015;Jin et al 2016;Paswan et al 2018;Li et al 2021). Furthermore, the study by Lofthouse et al (2017) has also shown an evidence of minor-merger in their two GPs.…”
Section: Discussionmentioning
confidence: 92%
“…Our blueberry galaxy has disturbed kinematics, showing a misalignment of ∼ 30 o between the stellar and gaseous kinematic major axes. In general, such kinematic misalignment in galaxies indicates signs of galaxy interaction and merger or external gas accretion (Jaiswal & Omar 2013;van de Voort et al 2015;Jin et al 2016;Paswan et al 2018;Li et al 2021). Furthermore, the study by Lofthouse et al (2017) has also shown an evidence of minor-merger in their two GPs.…”
Section: Discussionmentioning
confidence: 92%
“…Specifically, Thorp et al (2019) found a centrally-peaked SFR enhancement and general metallicity suppression in MaNGA star-forming post-mergers; while Pan et al (2019) found that the SFR enhancement in SFGs pairs emerges after the first encounter. In addition, morphologically, Li et al (2021) found a higher pair fraction in both SFGs and quiescent galaxies that show misaligned gas-stellar rotation. Feng et al (2020) showed that galaxies in pairs have higher kinematic asymmetry.…”
Section: Introductionmentioning
confidence: 89%
“…In the last decades, several formation scenarios of gas-star misalignments have been proposed, including external gas accretion from dwarf companions as well as cosmic webs (Thakar & Ryden 1998;Chen et al 2016;Jin et al 2016), minor/major mergers (Naab et al 2014;Li et al 2020). Recent simulations (Starkenburg et al 2019;Duckworth et al 2020c;Koudmani et al 2021) find a higher incidence of AGN in misaligned galaxies, suggesting AGN feedback also plays a role in the formation of misalignment.…”
Section: Formation Scenarios Of Misaligned Galaxiesmentioning
confidence: 99%